2014
DOI: 10.1111/jop.12255
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of matrix metalloproteinases (MMP‐3 and MMP‐9) in the pathogenesis of irinotecan‐induced oral mucositis

Abstract: These findings suggest vital roles played by MMP-3 and MMP-9 during OM pathophysiology. Further research is required to investigate the role of other MMPs and the naturally existing tissue inhibitors of MMPs. Research should also be directed to investigate beneficial effects of MMPs intervention therapies to prevent or reduce the severity of OM.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
32
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 31 publications
(33 citation statements)
references
References 37 publications
1
32
0
Order By: Relevance
“…[35]. Recent research has also shown elevated MMP-9 expression in the ventral surface of the tongue of tumour-bearing rats treated with chemotherapy [27]. These parallel earlier research showing a time dependent increase in both MMP-2 and MMP-9 in the jejunum following irinotecan administration [34].…”
supporting
confidence: 65%
See 3 more Smart Citations
“…[35]. Recent research has also shown elevated MMP-9 expression in the ventral surface of the tongue of tumour-bearing rats treated with chemotherapy [27]. These parallel earlier research showing a time dependent increase in both MMP-2 and MMP-9 in the jejunum following irinotecan administration [34].…”
supporting
confidence: 65%
“…Epithelial thickness was measured ten times across the width of the tissue section and an average determined [27]. All analysis was conducted in a blinded fashion.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Tumor invasion and metastasis markers. Tumor cells break through the extracellular matrix and basement membrane, which is an important step during the process of tumor invasion and metastasis (65). Many matrix metallo proteinases (MMPs) play significant roles in this process, including MMP-1, -2, -7, -9, -10, -12, -13, -14, -19, and -26 (66)(67)(68).…”
Section: Tumor Suppressor Markers (Antitumor Defense and Apoptosis)mentioning
confidence: 99%